2017
DOI: 10.1037/apl0000209
|View full text |Cite
|
Sign up to set email alerts
|

Eating your feelings? Testing a model of employees’ work-related stressors, sleep quality, and unhealthy eating.

Abstract: Although organizational research on health-related behaviors has become increasingly popular, little attention has been paid to unhealthy eating. Drawing on the self-regulation perspective, we conducted 2 daily diary studies to examine the relationships between work-related stressors, sleep quality, negative mood, and eating behaviors. Study 1 sampled 125 participants from 5 Chinese information technology companies and showed that when participants experienced higher levels of job demands in the morning, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(147 citation statements)
references
References 143 publications
5
138
2
Order By: Relevance
“…Moreover, we found that the interaction between work-related smartphone use and self-control demands is moderated by sleep quality: On days when employees experience high sleep quality after having used their smartphones for work intensively, next-day self-control processes at work and associated levels of ego depletion are no longer affected. This evidence is consistent with previous studies demonstrating that sleep ensures returning to work with restored self-control resources on the next day [31,32]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, we found that the interaction between work-related smartphone use and self-control demands is moderated by sleep quality: On days when employees experience high sleep quality after having used their smartphones for work intensively, next-day self-control processes at work and associated levels of ego depletion are no longer affected. This evidence is consistent with previous studies demonstrating that sleep ensures returning to work with restored self-control resources on the next day [31,32]. …”
Section: Discussionsupporting
confidence: 93%
“…For instance, Diestel and colleagues [30] found that sleep quality diminishes the impact of emotional dissonance on daily psychological well-being (ego depletion, need for recovery, and work engagement). Liu and colleagues [31] further revealed that the association between customer mistreatment and unhealthy eating (as an indicator of self-control failure) becomes weaker as a function of sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, based on research on resource recovery, one way to help employees replenish resources is to encourage them to “recharge” themselves sufficiently the night before morning commute. For example, employees could be made aware that lack of sleep could negatively impact their self‐control on the subsequent day (e.g., Barnes, Lucianetti, Bhave, & Christian, ; Barnes, Schaubroeck, Huth, & Ghumman, ; Barnes & Wagner, ; Y. Liu et al., ). Employees can be provided with information that the quality as well as quantity of sleep could be improved by establishing a routine for going to bed at the same time, refraining from eating or drinking food with caffeine or alcohol, and reducing smartphone use (Lanaj et al., ; Sonnentag et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study that should be addressed by future research is to specifically examine the role of negative affective state in commuting stress process and its impact on work. We did not theorize or test the effect of negative affective state, given that the process relating stressor, negative mood, and strain can be quite complicated and dynamic in nature (e.g., Fuller et al., ; Y. Liu et al., ). Future research could examine the role of negative affect state in the commuting stress process by using computational modeling approach coupled with intensive longitudinal data collection (Wang et al., ; Wang, Zhou, & Zhang, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation